The status of public libraries in the Philippines with special reference to provincial and city libraries - David, Conrado D. (1974)
This paper deals extensively on the actual conditions obtaining in thirty-three provincial and nineteen regularly organized city libraries administered and supervised by the National Library thru its Extension Division. The study includes such aspects of the public library as building, equipment, collection, readership, personnel, and the budget, and the financial support given to it by the local officials.